Laser-induced breakdown spectroscopy as a novel readout method for nanoparticle-based immunoassays - Modlitbová, Pavlína; Farka, Zdeněk; Pastucha, Matěj; Pořízka, Pavel; Novotný, Karel; Skládal, Petr; Kaiser, Jozef (Mikrochimica acta, 2019)
Laser-induced breakdown spectroscopy (LIBS) was examined as a novel method for readout of microtiter plate immunoassays involving nanoparticles (NP). The so-called Tag-LIBS technique is a sensitive method for the detection of specific biomarkers. It was applied to the determination of NP labels using nanosecond ablation sampling. The NP labels were examined from the bottom of a standard 96-well microtiter plate. Thanks to the flexibility of LIBS instrumentation, both the plasma emission collection and the focusing optics arrangements can be collinearly arranged. The experiments showed that silver NPs and gold NPs can be readily quantified on the bottom of the microtiter plate. Utilizing this technique, a sandwich immunoassay for human serum albumin using streptavidin-coated AgNP labels was developed. The assay has a 10 ng·mL-1 detection limit which is comparable to the sensitivity of fluorometric readout. The main advantage of this LIBS technique is its wide scope in which it enables a detection of almost any type of NP labels, irrespective to any fluorescence or catalytic properties. Owing to the immediate signal response, the relatively simple instrumentation also enables assay automation. The LIBS capability of multi-elemental analyses makes it a promising and fast alternative to other readout techniques, in particular with respect to multiplexed detection of biomarkers. Graphical abstract Laser-induced breakdown spectroscopy (LIBS) is used as a novel readout method of nanoparticle-based immunoassays in microtiter plates. After formation of sandwich immunocomplex, the analyte concentration is quantified as the signal of Ag nanoparticle labels determined by LIBS.
Keywords: lasery; Metal Nanoparticles; Immunoassay; Humans; Particle Size; stříbro; kovové nanočástice; Lasers; Gold; imunoanalýza; lidský sérový albumin; Surface Properties; Silver; biologické markery; velikost částic; lidé; Serum Albumin, Human; povrchové vlastnosti; Biomarkers; zlato